Integrating Peer Feedback and Digital Flashcards in Writing Recount Text at Junior High School: A Case Study - Rahayu, Ayu Puji; Rohayati, Dedeh; Sugiarto, Bambang Ruby (Universitas Galuh, 2025)
While peer feedback has increased exponentially in recent decades, especially in English as foreign language writing classes, little attention has been paid to 1) framing peer feedback as part of multiple frames of written class; and 2) processed learning behaviors while emerging picture-based as visual assistance into account for young EFL learners in high school. It picked the interest of the writer to conduct a study to investigate the use of peer feedback and digital flashcards in teaching writing recount text. This study aims 1) to figure out the teacher’s steps in integrating peer feedback and digital flashcards in teaching writing recount text; and 2) to find out how students experienced it in the class. This study employed a qualitative method with a case study design and data were collected through observation, interview, and students’ documents of recount text. Observation data was analyzed using thematic analysis; interview result was transcribed reduced, categorized and interpreted; and students’ document recount text were analyzed to confirm the generic structure of recount text. The participants were the English teacher and 20 students experienced in learning writing recount text by integrating peer feedback and digital flashcards. The findings revealed that the English teacher integrated peer feedback and digital flashcards in teaching recount text in the eighth grade at an Integrated Islamic Junior High School in Pangandaran. The findings also showed that students felt peer feedback and digital flashcards positively affected their motivation to write recount text and improve their writing skills, especially writing recount text. Based on the findings, it was established that peer feedback and digital flashcards can be used as a teaching method to motivate students in writing recount text. In addition, it was a beneficial framework to stimulate them to produce better text easier and more engaging way. The writer suggests further research to examine the related topic on other aspects of English at different levels and with different numbers of participants.